Analisis Pengaruh Manajemen Kas Dan Rasio Keuangan Daerah Terhadap Keputusan Investasi Pemerintah Daerah(Studi Kasus pada Pemerintah Kabupaten atau Kota di Jawa Tengah tahun 2011-2013) - Aditya, Yovica Kukuh Rian; , Dr. Zulfikar, SE, M.Si (2016)
This study aimed to analyze and prove the effect of Cash Management and Financial Ratios The area of the Local Government Investment Decisions case studies on local government or town in Central Java period from 2011 until 2013. The study sample consisted of 15 Districts and 4 Cities registered in Central Java period of 2011 through 2013 to certain criteria. The sampling method using purposive sampling. The data obtained from the study of Balance and Budget Realization Report (LRA) in the relevant audited by the auditors to come from the Directorate General of Audit in http://djpk.kemenkeu.go.id web sites, and to download the Financial Statements of the respective profile -masing district or city sampled. Data analysis techniques in this study using multiple linear regression analysis. Hypothesis testing using t statistics used in this study to test the partial regression coefficients and F test to test the truth of influence together with the level of significance 5%. In addition, all variables have been tested with Normality Test, Test Multicolinearity, Heteroskidastity Test and Test of Multiple Regression Analysis. The results of this study indicate that all variables passed the test classic assumptions and fit for use as research data. Statistical t test results showed that the variables of Cash Management, Earning Power of Total Investment, Investment Rate of Return does not significantly influence Investment Decisions, while the variable Debt to Equity Ratio and Debt to Total Assets Ratio significant influence terjadap Investment Decision.